2018
DOI: 10.4314/ijbcs.v12i2.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fish meal substitution with lima bean meal on growth and feed utilization in common carp fry, <i>Cyprinus carpio</i>

Abstract: An experiment was conducted in an earthen pond in the west region of Cameroon to investigate the level of replacing fish meal (FM) with lima bean meal (LBM) on zootechnic parameters in common carp fry. Four hundred and fifty fish weighing 0.91±0.03 g were divided into five groups of 90 fish each. In control group (LBM-0), fish received normal feed, while in four experimental groups, FM was replaced with LBM at 10%, 20%, 30% and 40% corresponding to LBM-10, LBM-20, LBM-30 and LBM-40. Fish were fed three times d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
3
2
0
Order By: Relevance
“…The average values of water quality parameters such as temperature, transparency, pH, dissolved oxygen, nitrite, nitrate, and ammonia monitored throughout the trials were considered as suitable for the survival, normal growth, as well as good general physiology of O. niloticus. These values were in accordance with the findings of Yoo and Lee, 2016, Makori et al 2017and Nyadjeu et al (2018 and could partially justify the absence of mortality observed throughout the study, coupled with experimental fish's apparent good health observed through the results on both the growth and feed utilization.…”
Section: Discussionsupporting
confidence: 90%
“…The average values of water quality parameters such as temperature, transparency, pH, dissolved oxygen, nitrite, nitrate, and ammonia monitored throughout the trials were considered as suitable for the survival, normal growth, as well as good general physiology of O. niloticus. These values were in accordance with the findings of Yoo and Lee, 2016, Makori et al 2017and Nyadjeu et al (2018 and could partially justify the absence of mortality observed throughout the study, coupled with experimental fish's apparent good health observed through the results on both the growth and feed utilization.…”
Section: Discussionsupporting
confidence: 90%
“…These results indicate that Heterobranchus longifilis juveniles have successfully used nutrients from the hyacinth meal. These results are in agreement with those obtained by some authors (Sivani et al 2013;Staykov et al 2015;Nyadjeu et al 2018) who found that the partial substitution of plant sources in fish diets improved growth performance of fish. Indeed, growth increased with increase in Eichhorniacrassipes leaf meal up to 30% incorporation.…”
Section: Discussionsupporting
confidence: 93%
“…Results from the current study indicates that substitution of fish meal (FM) with Lima bean meal (LBM) at 25% (D25) and 50% (D50), just like Coppens feed, significantly increased the growth in C. gariepinus fingerlings, compared to those fed with the normal diet and diet in which FM was completely replaced with LBM. These results are in conformity with those obtained by Nyadjeu et al (2018) on the effect of fish meal substitution with Lima bean meal on growth and feed utilization in common carp fry (Cyprinus carpio). Therefore, the results demonstrate that partial substitution of FM with LBM enhances nutrient utilization in C. gariepinus fingerlings, which was reflected in improved weight gain, specific growth rate, feed intake, feed conversion ratio, protein intake, and protein efficiency ratio.…”
Section: Discussionsupporting
confidence: 91%